Social accessibility of Kedai Rakyat 1Malaysia among low income group in urban Penang, Malaysia - Rosli, Hafizah; Samat, Narimah; Ghazali, Suriati (2015)

(untitled)
With increasingly higher cost of living in urban areas, various strategies have been undertaken to ease the financial burden, especially of the low income population residing in urban areas. The Malaysian Government, for example, has launched an affordable community shop program, known as Kedai Rakyat 1Malaysia (KR1M), that sells goods with quality comparable to those available at supermarkets or other retail stores but priced at 30 to 40 percent cheaper than the latter. However, previous studies have shown that these stores are less popular among the low income population as their locations are less accessible. There is also the stigma of being associated with poor migrant workers. This study takes into consideration distance as a factor in shopping at KR1M. Therefore it aims to investigate whether stigma has hindered low income population from shopping at KR1M. A quantitative survey was conducted on 57 households of Flat Taman Seri Pinang, Teluk Air Tawar, Butterworth, Pulau Pinang, which is located approximately 290 metres away from the KR1M. The findings indicated that the majority of low income respondents, with monthly household income ranging between RM1,001 and RM2,000 did visit KR1M. Furthermore, more than 60 per cent of the respondents strongly disagreed that stigma has led them to be ashamed of shopping at KR1M. The findings indicated that most of the respondents would choose to shop at the nearest groceries stores Thus, in planning for more KR1M in the future, location should be taken into consideration to make it more accessible to the targeted group.